2007
DOI: 10.1074/jbc.m701774200
|View full text |Cite
|
Sign up to set email alerts
|

A Six-membrane-spanning Topology for Yeast and Arabidopsis Tsc13p, the Enoyl Reductases of the Microsomal Fatty Acid Elongating System

Abstract: The very long chain fatty acids are crucial building blocks of essential lipids, most notably the sphingolipids. These elongated fatty acids are synthesized by a system of enzymes that are organized in a complex within the endoplasmic reticulum membrane. Although several of the components of the elongase complex have recently been identified, little is known about how these proteins are organized within the membrane or about how they interact with one another during fatty acid elongation. In this study the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
5
25
0
1
Order By: Relevance
“…There have, however, been no reports of the functions of VAC8 or TSC13 orthologues in any filamentous fungus to date. The M. oryzae MoTsc13p showed 60.1% identity to S. cerevisiae Tsc13p, with six predicted transmembrane domains (Figure 2 C), consistent with the topology of S. cerevisiae Tsc13p [38]. MoTsc13p has conserved amino acids (Figure S1 B), essential for activity of Tsc13p [38] (Genbank JN977614).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…There have, however, been no reports of the functions of VAC8 or TSC13 orthologues in any filamentous fungus to date. The M. oryzae MoTsc13p showed 60.1% identity to S. cerevisiae Tsc13p, with six predicted transmembrane domains (Figure 2 C), consistent with the topology of S. cerevisiae Tsc13p [38]. MoTsc13p has conserved amino acids (Figure S1 B), essential for activity of Tsc13p [38] (Genbank JN977614).…”
Section: Resultssupporting
confidence: 62%
“…The M. oryzae MoTsc13p showed 60.1% identity to S. cerevisiae Tsc13p, with six predicted transmembrane domains (Figure 2 C), consistent with the topology of S. cerevisiae Tsc13p [38]. MoTsc13p has conserved amino acids (Figure S1 B), essential for activity of Tsc13p [38] (Genbank JN977614). Importantly, we were unable to find a homologue of S. cerevisiae NVJ1 , using either nucleotide or amino acid sequences of NVJ1 , based on BLASTP or TBLASTN analysis, in the M. oryzae genome database, or by immuno-precipitation which we used to identify proteins interacting with MoVac8-GFP (data not shown).…”
Section: Resultssupporting
confidence: 62%
“…C, the predicted membrane topology of the TER enzyme with the P182L mutation site (*) is shown. The prediction was made based on the topology of the yeast and Arabidopsis homologs (20).…”
Section: Methodsmentioning
confidence: 99%
“…Although the membrane topology of the mammalian TER enzyme has not been determined, it is highly likely that this enzyme is an integral membrane protein with six membrane-spanning domains and cytosolic N and C termini (Fig. 1C) as deduced from the membrane topology of the yeast and Arabidopsis TER homologs (20). In this topology model, the Pro-182 residue is positioned in the second luminal loop.…”
mentioning
confidence: 99%
“…With the exception of a recently characterized elongase from the marine parasitic protozoon Perkinus marinus, all of the elongases that are involved in LCPUFA biosynthetic pathways are of the ELO/SUR4 gene family (Venegas-Caleron et al 2007). Of the remaining proteins involved in elongation, putative beta-ketoacyl-CoA reductases Han et al 2002) and enoyl-CoA reductases (Gable et al 2004;Paul et al 2007) have been suggested for yeast and plants. Recently, the PHS1 gene has been suggested to be responsible for the dehydration reaction in yeast (Denic and Weissman 2007).…”
Section: Epa Production In Plants Via the D6 Desaturase Pathwaymentioning
confidence: 99%